Pemberdayaan Masyarakat Pondok Pesantren Berbasis Pengembangan Lembaga Keuangan Mikro Syariah : Studi Kasus pada Pondok Pesantren Darussalam Dukuhwaluh Kabupaten Banyumas - Riyadi, Sugeng; Akhmadi, Slamet (el-Jizya: Jurnal Ekonomi Islam, 2022)
The pro-life skills movement towards Islamic boarding schools is quite encouraging. This is marked by a pro-active policy from the government that is more open in order to prepare pesantren alumni to take part in development participation. However, in the opinion of researchers, the opportunities provided are still independent grants. The point is, the government assistance is still in the form of mere material funds in the form of various entrepreneurial competitions as well as freelance fund faucets that emphasize the connectivity of Islamic boarding schools to the government and are non-auditing. Of course, this phenomenon will later lead to the pretension of unhealthy competition, stigma of nepotism and lead to apathy among Islamic boarding schools that are not covered by grant funds for these various government programs. On the other hand, the absence of auditing efforts on the progress of entrepreneurship assistance will cause the recipients of funds to be indifferent to the consequences of productivity and accountability. This discourse certainly requires an accurate integrative solution called continuous mentoring.